(untitled) (Atti del Sodalizio Glottologico Milanese, 2017)
In the fourth century Palestine is reopened to pilgrimages and travel. The Itinerarium Burdigalense (A. 333 A.D.) is a guide for travelers and pilgrims who come from Burdigala (=Bordeaux ) in Jerusalem, a itinerarium ad loca sancta inserted in a secular itinerarium. The itinerary is divided into two parts. The annotated stations are of three types: civitas, mansio, mutatio. The central part of the itinerary includes descriptive notes of the holy places. The pilgrim welcomes Jewish and Christian traditions and legends linked to places visited. In this article are studied some celtic place names in –magus and in –dunum that are located in the Itinerarium Burdigalense. KEYWORDS: toponyms, Latin, Itinerarium Burdigalense, word-formation, Celtic toponyms